2019
DOI: 10.1186/s42826-019-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol modulates the Akt/GSK-3β signaling pathway in a middle cerebral artery occlusion animal model

Abstract: Cerebral ischemia is a major cause of neurodegenerative disease. It induces neuronal vulnerability and susceptibility, and leads to neuronal cell death. Resveratrol is a polyphenolic compound that acts as an anti-oxidant. It exerts a neuroprotective effect against focal cerebral ischemic injury. Akt signaling pathway is accepted as a representative cell survival pathway, including proliferation, growth, and glycogen synthesis. This study investigated whether resveratrol regulates Akt/glycogen synthase kinase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Among them, 86 records were excluded due to review, abstracts without full text, not having purified resveratrol, no in vivo experiment, not reporting the number of animals in groups, and or no adequate outcomes (infarction volume or functional outcome determined by neurobehavioral score measured on any scale/rotarod test). Therefore, 54 studies ( Huang et al, 2001 ; Sinha et al, 2002 ; Inoue, 2003 ; Gao et al, 2006 ; Tsai et al, 2007 ; Dong et al, 2008 ; Yousuf et al, 2009 ; Li et al, 2010 ; Sakata et al, 2010 ; Shin et al, 2010 ; Ren et al, 2011 ; Li et al, 2012 ; Shin et al, 2012 ; Hurtado et al, 2013 ; Lanzillotta et al, 2013 ; Lin et al, 2013 ; Orsu et al, 2013 ; Yan et al, 2013 ; Saleh et al, 2014 ; Wang et al, 2014 ; Fang et al, 2015 ; Hermann et al, 2015 ; Ishrat et al, 2015 ; Koronowski et al, 2015 ; Li et al, 2015 ; Narayanan et al, 2015 ; Pandey et al, 2015 ; Pang et al, 2015 ; Abdel-Aleem et al, 2016 ; Jeong et al, 2016 ; Li et al, 2016 ; Lopez et al, 2016 ; Su et al, 2016 ; Wan et al, 2016 ; Yang et al, 2016 ; Al Dera, 2017 ; He et al, 2017 ; Koronowski et al, 2017 ; Yu et al, 2017 ; Faggi et al, 2018 ; Hou et al, 2018 ; Liu et al, 2018 ; Dou et al, 2019 ; Grewal et al, 2019 ; Park et al, 2019 ; Yan et al, 2019 ; Alquisiras-Burgos et al, 2020 ; Lu et al, 2020 ; Mota et al, 2020 ; Pineda-Ramírez et al, 2020 ; Teertam et al, 2020 ; Yao et al, 2020 ; McDonald...…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 86 records were excluded due to review, abstracts without full text, not having purified resveratrol, no in vivo experiment, not reporting the number of animals in groups, and or no adequate outcomes (infarction volume or functional outcome determined by neurobehavioral score measured on any scale/rotarod test). Therefore, 54 studies ( Huang et al, 2001 ; Sinha et al, 2002 ; Inoue, 2003 ; Gao et al, 2006 ; Tsai et al, 2007 ; Dong et al, 2008 ; Yousuf et al, 2009 ; Li et al, 2010 ; Sakata et al, 2010 ; Shin et al, 2010 ; Ren et al, 2011 ; Li et al, 2012 ; Shin et al, 2012 ; Hurtado et al, 2013 ; Lanzillotta et al, 2013 ; Lin et al, 2013 ; Orsu et al, 2013 ; Yan et al, 2013 ; Saleh et al, 2014 ; Wang et al, 2014 ; Fang et al, 2015 ; Hermann et al, 2015 ; Ishrat et al, 2015 ; Koronowski et al, 2015 ; Li et al, 2015 ; Narayanan et al, 2015 ; Pandey et al, 2015 ; Pang et al, 2015 ; Abdel-Aleem et al, 2016 ; Jeong et al, 2016 ; Li et al, 2016 ; Lopez et al, 2016 ; Su et al, 2016 ; Wan et al, 2016 ; Yang et al, 2016 ; Al Dera, 2017 ; He et al, 2017 ; Koronowski et al, 2017 ; Yu et al, 2017 ; Faggi et al, 2018 ; Hou et al, 2018 ; Liu et al, 2018 ; Dou et al, 2019 ; Grewal et al, 2019 ; Park et al, 2019 ; Yan et al, 2019 ; Alquisiras-Burgos et al, 2020 ; Lu et al, 2020 ; Mota et al, 2020 ; Pineda-Ramírez et al, 2020 ; Teertam et al, 2020 ; Yao et al, 2020 ; McDonald...…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, in normal brain tissue during ischemia/reoxygenation, there is a need to suppress the processes of necrosis and apoptosis. Our experiments showed that after incubation with SeNPs, not only complete inhibition of OGD/R-induced necrosis occurred but also an increase in the expression of PI3K and PKC, the role of which in suppressing apoptosis of brain cells is well known [ 44 , 45 , 46 , 47 , 48 ]. Our experiments have shown that incubation with SeNPs leads to suppression of IL-1β and Nf-κb expression after OGD/R exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Akt and mTOR overexpression improved the protective effects after cerebral ischemia-reperfusion injury in MCAO rats, suggesting that the activation of the PI3K/Akt/mTOR signaling pathway provides significant neuroprotective effects against cerebral ischemia-reperfusion injury. P-Akt and p-mTOR ( Li et al, 2016 ; Yang et al, 2017 ; Park et al, 2019 ; Sun et al, 2020 ) are commonly recognized as markers for activation of the PI3K/Akt/mTOR pathway. In the present study, the levels of p-AKT and p-mTOR were significantly decreased following I/R injury and were activated by TFCJ treatment.…”
Section: Discussionmentioning
confidence: 99%